Respuesta :

Answer:

[tex]-8(y+4) =(x-6)^{2}[/tex]  

Step-by-step explanation:

The standard form of a parabola is given by the following equation:

[tex](x-h)^{2} =4p(y-k)[/tex]

Where the focus is given by:

[tex]F(h,k+p)[/tex]

The vertex is:

[tex]V=(h,k)[/tex]

And the directrix is:

[tex]y-k+p=0[/tex]

Now, using the previous equations and the information provided by the problem, let's find the equation of the parabola.

If the focus is (-6,6):

[tex]F=(h,k+p)=(6,-6)[/tex]

Hence:

[tex]h=6\\\\k+p=-6\hspace{10}(1)[/tex]

And if the directrix is [tex]y=-2[/tex] :

[tex]-2-k+p=0\\\\k-p=-2\hspace{10}(2)[/tex]

Using (1) and (2) we can build a 2x2 system of equations:

[tex]k+p=-6\hspace{10}(1)\\k-p=-2\hspace{10}(2)[/tex]

Using elimination method:

(1)+(2)

[tex]k+p+k-p=-6+(-2)\\\\2k=-8\\\\k=-\frac{8}{2}=-4\hspace{10}(3)[/tex]

Replacing (3) into (1):

[tex]-4+p=-6\\\\p=-6+4\\\\p=-2[/tex]

Therefore:

[tex](x-6)^{2} =4(-2)(y-(-4)) \\\\(x-6)^{2} =-8(y+4)[/tex]

So, the correct answer is:

Option 3